2016
DOI: 10.1111/1751-2980.12385
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of lymph node metastasis in early gastric carcinomas diagnosed by WHO criteria in 379 Chinese patients

Abstract: LNM occurred in 12.9% of EGC diagnosed with the WHO criteria in Chinese patients. Independent risk factors of LNM were identified in early DGC only and included female sex, DGC, poorly cohesive carcinoma and lymphovascular invasion. Early PGC has a much lower risk for LNM than early DGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 37 publications
12
35
1
Order By: Relevance
“…More recently, Lee et al [26] reported a high (18.3%, 9/49) frequency of lymph node metastasis in early papillary adenocarcinoma of Korean patients. The abovementioned results have been confirmed most recently in Chinese patients [14,18]. Compared to early tubular adenocarcinoma, early papillary adenocarcinoma is associated with a significantly worse 5-year survival rate (80.5% compared to 96.8% in early tubular adenocarcinoma, p < 0.05), significantly more submucosal invasion (64.4 vs. 43.6%) ( p < 0.05), and the micropapillary growth pattern (6.8 vs. 0%) ( p < 0.003) [18].…”
Section: Worse Prognosis For Early Papillary Adenocarcinomamentioning
confidence: 57%
See 4 more Smart Citations
“…More recently, Lee et al [26] reported a high (18.3%, 9/49) frequency of lymph node metastasis in early papillary adenocarcinoma of Korean patients. The abovementioned results have been confirmed most recently in Chinese patients [14,18]. Compared to early tubular adenocarcinoma, early papillary adenocarcinoma is associated with a significantly worse 5-year survival rate (80.5% compared to 96.8% in early tubular adenocarcinoma, p < 0.05), significantly more submucosal invasion (64.4 vs. 43.6%) ( p < 0.05), and the micropapillary growth pattern (6.8 vs. 0%) ( p < 0.003) [18].…”
Section: Worse Prognosis For Early Papillary Adenocarcinomamentioning
confidence: 57%
“…The abovementioned results have been confirmed most recently in Chinese patients [14,18]. Compared to early tubular adenocarcinoma, early papillary adenocarcinoma is associated with a significantly worse 5-year survival rate (80.5% compared to 96.8% in early tubular adenocarcinoma, p < 0.05), significantly more submucosal invasion (64.4 vs. 43.6%) ( p < 0.05), and the micropapillary growth pattern (6.8 vs. 0%) ( p < 0.003) [18]. The cases with a micropapillary growth pattern were all associated with early papillary adenocarcinoma and had a high (50%, 2/4) nodal metastasis rate, though in a small sample [14,18].…”
Section: Worse Prognosis For Early Papillary Adenocarcinomamentioning
confidence: 57%
See 3 more Smart Citations